MicroRNAs Are Involved in Homocysteine-Induced Cardiac Remodeling - Mishra, Paras K. (2009)
Elevated level of homocysteine (Hcy) called hyperhomocysteinemia (HHcy) is one of the major risk factors for chronic heart failure. Although the role of Hcy in cardiac remodeling is documented, the regulatory mechanism involved therein is still nebulous. MicroRNAs (miRNAs) and dicer have been implicated in regulation of cardiovascular diseases. Dicer is the only known enzyme involved in miRNA maturation. We investigated the involvement of dicer and miRNA in Hcy-induced cardiac remodeling. HL-1 cardiomyocytes were cultured in different doses of Hcy. Total RNA was isolated and RT-PCR and real-time PCR was performed for dicer, MMP-2,-9, TIMP-1,-3, and NOX-4. MiRNA microarray was used for analyzing the differential expression of miRNAs. Individual miRNA assay was also done. Western blotting was used to assess the MMP-9 expression in HHcy cardiomyocytes. The RT-PCR results suggest that dicer expression is enhanced in HHcy cardiomyocytes suggesting its involvement in cardiac remodeling caused due to high dose of Hcy. On the other hand, high dose of Hcy increased NOX-4 expression, a marker for oxidative stress. Additionally, HHcy cardiomyocytes showed elevated levels of MMP-2,-9 and TIMP-1,-3, and reduced expression of TIMP-4, suggesting cardiac remodeling due to oxidative stress. The miRNA microarray assay revealed differential expression of 11 miRNAs and among them miR-188 show dramatic downregulation. These findings suggest that dicer and miRNAs especially miR-188 are involved in Hcy-induced cardiac remodeling.